Investigation of the discrete fragmentation of 18S rRNA in the composition of 40S ribosomal subunits of plant cells (Experimental biology, 2015)
This paper studies the phenomenon of discrete fragmentation of 18S rRNA molecule it the composition of small (40S)ribosomal subunits of plant cells. It was revealed that in total RNA preparations isolated from wheat germ continuouslydetects small cytoplasmic RNA of about 100 nucleotides corresponding to the 3’-terminal fragment of 18S RNA. This 3’-terminal fragment of the 18S rRNA was detected in plant cells belonging to different taxa, as well as in animal cells,so that the investigated process of discrete 18S rRNA fragmentation should be sufficiently universal phenomenon. It was established that the content of investigated 18S rRNA fragment is much lower in young plant shoots rather than in dry and germinating seeds, and that its content increases if germinated seeds were exposed to heat shock (37° C). It is suggested that this type of 18S rRNA fragmentation is one of the ways of protein synthesis deregulation by disrupting the integrity of ribosomal RNA and separation of relationships between its structural and functional domains.
Keywords: descrete 18S rRNA fragmentation; heat shock; small cytoplasmic RNAs; plant 40S ribosomal subunits.